Cluster electrolyte, composite pole piece, preparation method of composite pole piece and lithium battery
By using cluster electrolytes in lithium batteries, the complexation reaction between organic electrolytes and solvents and high temperature or negative pressure treatment, the problem of volatility of existing electrolytes is solved, and a higher thermal stability and electrochemical window is achieved. Compatible with high-voltage positive electrode materials, reduces production costs and complexity, and is suitable for large-scale production of lithium batteries.
Patent Information
- Application Number
- CN202411243864.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-03
AI Technical Summary
The electrolytes of existing lithium batteries are prone to volatilization under high temperature or negative pressure conditions, resulting in thermal runaway and safety accidents, and are unable to be compatible with high voltage positive electrode materials, limiting the energy density and cycle life of lithium batteries.
Cluster electrolyte is used to complex the organic electrolyte lithium salt and organic solvent to form complex molecules, forming cluster electrolyte with solvated sheath layer, and combining high temperature or negative pressure treatment to remove volatile solvents to form stable electrolytes .
It improves the thermal stability and safety of lithium batteries, expands the electrochemical window, is compatible with high-voltage positive electrode materials, and reduces production costs and preparation complexity, making it suitable for large-scale production.
Smart Images

Figure CN119253057A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to a cluster electrolyte, a composite electrode and a preparation method thereof, and a lithium battery. Background Art
[0002] With the rapid development of new energy vehicles and large-scale energy storage, people have also put forward higher performance requirements for lithium batteries, including higher energy density, longer cycle life and higher safety. Among the various factors that affect the performance of lithium batteries, electrolyte, as the "blood" of lithium batteries, plays a role in transporting lithium ions inside lithium batteries and is one of the key factors that determine the performance of lithium batteries.
[0003] Therefore, it is necessary to develop an electrolyte that is compatible with high energy density positive and negative electrode materials, has good thermal stability and electrochemical properties, and also has the characteristics of low production cost, simple and easy to control preparation process. Summary of the invention
[0004] The purpose of this application is to provide a cluster electrolyte that is compatible with high energy density positive and negative electrode materials, has good thermal stability and electrochemical properties, and also has the characteristics of low production cost, simple and easy-to-control preparation process, etc.
[0005] In a first aspect, the present application provides a cluster electrolyte, comprising: a complex molecule generated by a complex reaction between a cation of an organic electrolyte lithium salt and an organic solvent molecule, and an anion of the organic electrolyte lithium salt located in a solvation sheath of the cation.
[0006] In some embodiments, the organic electrolyte lithium salt includes at least one of lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium di(polyfluoroalkylsulfonyl)imide, lithium di(polyfluoroalkoxysulfonyl)imide, tri(trifluoromethylsulfonyl)methyl lithium, lithium bisoxalatoborate, and lithium difluorooxalatoborate.
[0007] In some embodiments, the organic solvent includes at least one of a carbonate solvent, a fluorocarbon solvent, an ether solvent, a fluoroether solvent, a carboxylate solvent, a sulfite solvent, a phosphate solvent, and a sulfone solvent.
[0008] In a second aspect, the present application provides a method for preparing a cluster electrolyte, comprising: dissolving an organic electrolyte lithium salt in an organic solvent to obtain a precursor; and heating and / or applying negative pressure to the precursor so that the organic solvent molecules in the precursor combine with the electrolyte lithium salt to form a cluster electrolyte, and the organic solvent that has not formed the cluster electrolyte is completely volatilized, wherein the cluster electrolyte includes complex molecules generated by complex reaction between cations of the organic electrolyte lithium salt and the organic solvent molecules, and anions of the organic electrolyte lithium salt located in the solvation sheath of the cations.
[0009] In some embodiments, the organic electrolyte lithium salt includes at least one of lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium di(polyfluoroalkylsulfonyl)imide, lithium di(polyfluoroalkoxysulfonyl)imide, tri(trifluoromethylsulfonyl)methyl lithium, lithium bisoxalatoborate, and lithium difluorooxalatoborate.
[0010] In some embodiments, the organic solvent includes at least one of a carbonate solvent, a fluorocarbon solvent, an ether solvent, a fluoroether solvent, a carboxylate solvent, a sulfite solvent, a phosphate solvent, and a sulfone solvent.
[0011] In some embodiments, the step of dissolving the organic electrolyte lithium salt in an organic solvent to obtain a precursor further includes adding an additive to the organic solvent, wherein the additive includes at least one of a performance optimizer and a flame retardant.
[0012] In some embodiments, the performance optimizer includes vinylene carbonate, vinyl ethylene carbonate, ethylene sulfate, ethylene sulfite, propylene sulfate, propylene sulfite, 4-methylethylene sulfate, 4-methylethylene sulfite, 1,4-butane sultone, 1,3-propane sultone, cyclohexylbenzene, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(trimethylsilyl)borate, succinonitrile, adiponitrile, pentafluoropropionic anhydride, fluoroethylene carbonate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide) , lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorophosphate and lithium nitrate; and / or the flame retardant includes at least one of tris(2,2,2-trifluoroethyl)phosphite, tris(4-fluorophenyl)phosphine, tris(2,2,3,3,3-pentafluoropropyl)phosphate, triphenyl phosphite, trimethyl phosphite, triethyl phosphite, tributyl phosphite, dimethyl methylphosphonate, diethyl ethylphosphonate, ethoxypentafluorocyclotriphosphazene, phenoxypentafluorocyclotriphosphazene, hexamethoxycyclotriphosphazene and ionic liquid.
[0013] In a third aspect, the present application provides a method for preparing a composite electrode, comprising: uniformly dry-mixing a cluster electrolyte with an electrode active material and a conductive agent to obtain a first mixture; adding a binder to the first mixture and applying high shear force to mix the mixture to fiberize the binder to obtain a second mixture; rolling or extruding the second mixture to obtain a self-supporting electrode film; hot-pressing the self-supporting electrode film and a current collector to obtain a composite electrode; and die-cutting the composite electrode to obtain the composite electrode.
[0014] In some embodiments, the electrode active material is a positive electrode active material or a negative electrode active material; the positive electrode active material includes at least one of lithium cobalt oxide, high-pressure lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium-rich manganese-based material and lithium manganese oxide, and the negative electrode active material includes at least one of carbon-based material, silicon-based material, silicon-carbon composite material, lithium titanate, tin-based material, germanium-based material and black phosphorus-based material; and / or the conductive agent includes at least one of electric carbon black, carbon nanotubes, nano-carbon fibers and graphene; the binder includes polytetrafluoroethylene; and / or the current collector is copper foil, aluminum foil, nickel foil, stainless steel foil or conductive plastic film;
[0015] In a fourth aspect, the present application provides a composite pole piece prepared by the preparation method described in the third aspect of the present application.
[0016] In a fifth aspect, the present application provides a lithium battery, comprising at least two composite electrodes as described in the fourth aspect of the present application; and a diaphragm arranged between the composite electrodes, wherein the diaphragm is a solid electrolyte diaphragm or a quasi-solid electrolyte diaphragm.
[0017] The beneficial effects of the cluster electrolyte, composite electrode, preparation method thereof, and lithium battery provided in this application include but are not limited to the following:
[0018] Compared with liquid electrolytes and gel electrolytes, the cluster electrolyte provided in this application has higher thermal stability and safety, a wider electrochemical window, and is compatible with high-voltage positive electrode materials; compared with solid electrolytes, it has low production costs, a simple and easy-to-control preparation process, and is easy to achieve large-scale production.
[0019] The lithium battery prepared by the composite electrode including the cluster electrolyte provided in the present application has better thermal stability and safety than conventional liquid lithium batteries; compared with solid-state batteries, the production cost is low and large-scale production is easy to achieve.
[0020] In addition, the preparation method of lithium batteries using composite pole pieces is simpler than that of conventional liquid lithium batteries, reduces the liquid injection process, and helps to improve production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The following figures describe in detail the exemplary embodiments disclosed in this application. The same reference numerals represent similar structures in several views of the drawings. Those skilled in the art will understand that these embodiments are non-limiting, exemplary embodiments, and the drawings are only for the purpose of illustration and description, and are not intended to limit the scope of this application. Other embodiments may also accomplish the inventive intent in this application. It should be understood that the drawings are not drawn to scale.
[0022] in:
[0023] Figure 1 is a flow chart of a method for preparing a cluster electrolyte according to some embodiments of the present application; and
[0024] Figure 2 The present invention is a flow chart of a method for preparing a composite pole piece according to some embodiments of the present application. DETAILED DESCRIPTION
[0025] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.
[0026] According to the form of the electrolyte, lithium battery electrolytes can be roughly divided into liquid electrolytes, gel electrolytes and solid electrolytes.
[0027] Conventional lithium batteries use flammable liquid organic electrolytes as battery electrolytes. The advantage of liquid organic electrolytes is that they have high room temperature ionic conductivity (about 10 -2 S / cm), the disadvantage is that in the case of battery abuse, the liquid organic electrolyte is easy to volatilize and react with the electrode material, accelerating the thermal runaway of the battery, causing the battery to burn or even explode and other safety accidents; in addition, due to the narrow electrochemical window of conventional liquid organic electrolytes (<4.5V), they are not compatible with high-voltage positive electrode materials, so the energy density of the battery cannot be further improved.
[0028] Gel electrolytes are generally prepared by adding a small amount of polymerizable organic macromolecular monomers, crosslinking agents and initiators to liquid organic electrolytes, and initiating crosslinking polymerization of polymerizable macromolecular monomers under heating or light conditions to form gel electrolytes. Gel electrolytes have better thermal stability and mechanical properties than liquid electrolytes, and also have higher room temperature ionic conductivity (~10 -3However, the gel electrolyte still contains a large amount of liquid electrolyte components. Under the conditions of squeezing or high temperature, the liquid electrolyte will still leak or volatilize in large quantities, causing battery swelling or thermal runaway.
[0029] Solid electrolytes refer to compounds that have ionic conductivity in a solid state. Since they do not contain volatile liquid components, they have good thermal stability and mechanical properties. They are the core components of solid-state batteries and one of the current hot topics in the field of lithium battery research. According to the chemical composition and structure of solid electrolytes, solid electrolytes can be divided into three categories: polymer solid electrolytes, inorganic solid electrolytes, and composite solid electrolytes.
[0030] The first category is polymer solid electrolytes, which are composed of high molecular polymers and lithium salts. The representative polymer solid electrolyte is polyethylene oxide (PEO)-based solid electrolyte, whose conductive mechanism is the complexation of lithium ions with polar groups on the polymer chain. Under the action of the electric field, with the thermal motion of the molecular chain segments in the amorphous region, lithium ions and polar polymer groups continuously undergo a complexation-decomplexation process, thereby realizing the migration of lithium ions. The advantages of polymer electrolytes are light weight, good interface contact, and good film-forming properties. The disadvantages are low mechanical strength and narrow electrochemical window, which cannot be applied to high-voltage positive electrode materials. In addition, the room temperature ionic conductivity of polyethylene oxide (PEO)-based solid electrolytes is low (10 -7 ~10 -8 S / cm), which can hardly work at room temperature. Therefore, batteries using this solid polymer electrolyte need to operate normally at a higher temperature (≥60°C).
[0031] The second category is inorganic solid electrolytes. Inorganic solid electrolyte materials can be divided into inorganic oxide solid electrolytes, inorganic sulfide solid electrolytes and inorganic halide solid electrolytes. The conduction mechanism of inorganic solid electrolytes is that under the action of an electric field, lithium ions move through vacancies or lattice defects in the lattice structure, thereby achieving ion conduction. The advantages of inorganic oxide solid electrolytes are a wide electrochemical window, good thermal stability and mechanical stability, and good compatibility with positive and negative electrode materials. In addition, inorganic oxide solid electrolytes have good environmental stability and good chemical and electrochemical stability in the air. The disadvantage is that the room temperature ionic conductivity is relatively low (~10 -4 S / cm), which affects the rate performance of the battery; due to its high rigidity, the interface contact performance with the electrode material is poor, resulting in a large solid-solid contact interface resistance inside the electrode. In addition, the production of inorganic oxide solid electrolytes has high raw material and process costs, resulting in its high price. Large-scale use will significantly increase the production cost of the battery. The advantages of inorganic sulfide solid electrolytes are high room temperature ionic conductivity (~10 -3 -10 -2S / cm), and even comparable to the ionic conductivity of conventional liquid electrolytes, and soft texture, good interface contact with electrode materials. The disadvantages are a narrow electrochemical window, poor electrochemical compatibility with electrode materials, and easy side reactions; it is sensitive to water and oxygen in the air and easily produces highly toxic hydrogen sulfide gas, so the environmental control requirements for preparation and use are extremely high. In addition, the raw materials of inorganic sulfide solid electrolytes are expensive, resulting in high production and use costs, which is not conducive to large-scale application. The advantages of inorganic halide solid electrolytes are high oxidation stability and a wide electrochemical window, good compatibility with high-voltage positive electrode materials, and high room temperature ionic conductivity (~10 -3 S / cm). The disadvantage is that halide solid electrolytes use a large amount of precious metal rare earth elements (such as In, Sc, Y, etc.). When applied on a large scale, cost and element abundance are both limiting factors; halide solid electrolytes have poor compatibility with metal lithium anodes or lithium alloy anodes, so halide solid electrolytes cannot directly contact lithium metal anodes. Other strategies need to be adopted when applying them. In addition, the research and application of halide solid electrolytes are still in a relatively early stage, and further research and optimization are needed to achieve large-scale application.
[0032] The third category is composite solid electrolytes, usually polymer / inorganic composite solid electrolytes, which make comprehensive use of the conductive mechanisms and advantages of the above two types of solid electrolytes, and usually have higher room temperature ionic conductivity and better processing performance. However, the preparation method of this composite solid electrolyte is relatively complicated, and the preparation process and related equipment requirements are relatively high, resulting in high production and preparation costs, which limits its large-scale application.
[0033] The present application provides a cluster electrolyte, which includes complex molecules generated by complex reaction of cations of organic electrolyte lithium salt and organic solvent molecules, and anions of the organic electrolyte lithium salt located in the solvation sheath of the cations. The cluster electrolyte will not volatilize organic solvent gas under high temperature or negative pressure, has good thermal stability, is not easy to volatilize, has a wide electrochemical window, and has a simple and easy-to-control preparation process, which lays a good foundation for the development and large-scale application of high-performance lithium batteries.
[0034] The cluster electrolyte and the preparation method thereof provided in the present application will be described in detail below with reference to the embodiments and the accompanying drawings.
[0035] First, refer to Figure 1 The present application provides a method for preparing a cluster electrolyte, comprising: dissolving an organic electrolyte lithium salt in an organic solvent to obtain a precursor; and heating and / or applying negative pressure to the precursor so that the organic solvent molecules in the precursor combine with the electrolyte lithium salt to form the cluster electrolyte, and the organic solvent that has not formed the cluster electrolyte is completely volatilized.
[0036] The cluster electrolyte includes complex molecules generated by complexation reaction between cations of the organic electrolyte lithium salt and the organic solvent molecules, and anions of the organic electrolyte lithium salt located in the solvation sheath of the cations. The solvation sheath described in the present application refers to a layer of solvent molecules surrounding the lithium salt cations, i.e., lithium ions, and the organic solvent molecules are tightly combined with the lithium ions through complexation to form the solvation sheath.
[0037] The cluster electrolyte is a complexation reaction between lithium salt cations and organic solvent molecules, and at the same time, lithium salt anions enter the solvation sheath of lithium salt cations under the Coulomb force between lithium salt cations, so that "lithium salt cations-organic solvent molecules-lithium salt anions" are "bound" together to form a cluster electrolyte. The conductive mechanism of the cluster electrolyte is that under the action of the electric field, lithium ions in the cluster migrate from one lithium salt anion to another lithium salt anion with the assistance of the solvation sheath, thereby achieving ion conduction.
[0038] The cluster electrolyte proposed in this application has similar electrochemical properties to the high-concentration salt electrolyte. Both of them have a large amount of lithium salt and a small amount of organic solvent in chemical composition, but they have important differences in preparation method, volatility, solvent structure and usage method.
[0039] In terms of preparation method and volatility, the high-concentration salt electrolyte is directly mixed and stirred with a large amount of lithium salt and a small amount of organic solvent, so that the lithium salt is slowly dissolved to form a high-concentration salt electrolyte. The high-concentration salt electrolyte formed by this method still has a large volatility under high temperature or negative pressure conditions, so that it still has a large defect in thermal stability. The cluster electrolyte preparation method proposed in the present application is to first prepare an easily soluble low-concentration cluster electrolyte precursor, and then fully volatilize the organic solvent through a high temperature and / or negative pressure process, remove the volatile organic solvent part, and the remaining organic solvent forms a cluster with the lithium salt, which cannot continue to volatilize, so the cluster electrolyte formed has good thermal stability, and the electrode made therefrom will not volatilize the organic solvent gas under high temperature and / or negative pressure, so that the electrode and the battery have good thermal stability.
[0040] In terms of solvent structure, the high-concentration salt electrolyte is mainly composed of contact ion pairs and aggregates, but still contains a certain amount of lithium ions and solvent molecules to form solvent separation ion pairs and free solvent molecules. The separation ion pairs and free solvent molecules are also the reason why the high-concentration salt electrolyte is volatile under high temperature or negative pressure conditions. The cluster electrolyte proposed in this application has undergone a high temperature and / or negative pressure volatilization process, so that the organic solvent molecules are fully volatilized. The electrolyte formed by the remaining non-volatile organic solvent and lithium salt does not contain separation ion pairs and free solvent molecules, and all are cluster electrolytes.
[0041] In terms of usage, due to the high concentration of lithium salt in the high-concentration electrolyte (usually ≥4mol / L), its viscosity is relatively large, and it cannot completely penetrate into the internal pores of the electrode like a low-concentration electrolyte. Direct use will cause incomplete electrolyte penetration and uneven mixing with the electrode material. Even if the battery is heated, the problem cannot be completely eliminated. Therefore, a large amount of diluent is required to dilute the formation of a local high-concentration electrolyte before use, and the diluent usually has a low viscosity, a low boiling point, and a high volatility. Therefore, the battery using a local high-concentration electrolyte is prone to volatilization in large quantities under high temperature or negative pressure conditions, causing safety problems such as battery swelling and thermal runaway. The cluster electrolyte proposed in this application can be evenly mixed with various materials in the active material layer during the electrode preparation process, and there is no problem of being unable to fully penetrate into the interior of the electrode due to viscosity problems and being unevenly mixed with the electrode material.
[0042] In some embodiments, in the step of dissolving an organic electrolyte lithium salt in an organic solvent to obtain a precursor, the mass ratio of the organic electrolyte lithium salt to the organic solvent is (3-43):(57-97).
[0043] In some embodiments, the heating temperature is 30-120°C, for example, 30°C, 50°C, 70°C, 100°C or 120°C; and the heating time is 2-100h, for example, 2h, 10h, 50h, 80h or 100h.
[0044] In some embodiments, the negative pressure is applied by placing the precursor in a vacuum environment, such as a vacuum oven.
[0045] In some embodiments, the magnitude of the applied negative pressure is -0.02 MPa to -0.1 MPa, for example, -0.02 MPa, -0.05 MPa or -0.1 MPa.
[0046] In some embodiments, the organic electrolyte lithium salt includes at least one of lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium di(polyfluoroalkylsulfonyl)imide, lithium di(polyfluoroalkoxysulfonyl)imide, tri(trifluoromethylsulfonyl)methyl lithium, lithium bisoxalatoborate, and lithium difluorooxalatoborate.
[0047] In some embodiments, the organic solvent includes at least one of a carbonate solvent, a fluorocarbon solvent, an ether solvent, a fluoroether solvent, a carboxylate solvent, a sulfite solvent, a phosphate solvent, and a sulfone solvent.
[0048] In some embodiments, the carbonate solvent includes at least one of ethylene carbonate, 1,2-dimethylethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dibutyl carbonate and derivatives thereof.
[0049] In some embodiments, the fluorocarbonate solvent includes at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoromethylethylene carbonate, methyl trifluoroethyl carbonate, fluorodimethyl carbonate and derivatives thereof.
[0050] In some embodiments, the ether solvent includes at least one of tetrahydrofuran, dioxolane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether and derivatives thereof.
[0051] In some embodiments, the fluoroether solvent is a linear fluoroether with the structural formula: R 1 -OR 2 , where R 1 and R 2 It may be methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, isobutyl, tert-butyl, pentyl, isopentyl, etc., or a group in which some or all of the hydrogen atoms are substituted with fluorine.
[0052] In some embodiments, the fluoroether solvent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, 1,1,1,3,3,3-hexafluoropropyl-methyl ether, 1,1,1,2,3,3-hexafluoropropyl-2,2,3,3-tetrafluoropropyl ether and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether.
[0053] In some embodiments, the carboxylate solvent includes at least one of methyl formate, methyl acetate, ethyl acetate and derivatives thereof.
[0054] In some embodiments, the sulfite solvent includes at least one of dimethyl sulfite, diethyl sulfite and derivatives thereof.
[0055] In some embodiments, the phosphate ester solvent includes at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, ethylene ethyl phosphate and tris(2,2,2-trifluoroethyl) phosphate.
[0056] In some embodiments, the sulfone solvent includes at least one of dimethyl sulfoxide and sulfolane.
[0057] In some embodiments, the step of dissolving the organic electrolyte lithium salt in an organic solvent to obtain a precursor further includes adding an additive to the organic solvent, wherein the additive includes at least one of a performance optimizer and a flame retardant.
[0058] The performance optimizer is used to improve the ionic conductivity, electrochemical window and long cycle stability of the cluster electrolyte. In some embodiments, the performance optimizer includes vinylene carbonate, vinyl ethylene carbonate, ethylene sulfate, ethylene sulfite, propylene sulfate, propylene sulfite, 4-methylethylene sulfate, 4-methylethylene sulfite, 1,4-butane sultone, 1,3-propane sultone, cyclohexylbenzene, tris(trimethylsilane) phosphate, tris(trimethylsilane) phosphite, tris(trimethylsilane) borate, succinonitrile, adiponitrile, pentafluoropropionic anhydride, fluoroethylene carbonate, difluorooxalato lithium borate, bistrifluoromethanesulfonyl imide lithium, bisfluorosulfonyl imide lithium, lithium tetrafluoroborate, lithium bisoxalato borate, lithium difluorophosphate and lithium nitrate.
[0059] Since the cluster electrolyte may burn under extreme abuse conditions, adding the flame retardant can further improve the intrinsic safety of the cluster electrolyte. In some embodiments, the flame retardant includes at least one of tris(2,2,2-trifluoroethyl)phosphite, tris(4-fluorophenyl)phosphine, tris(2,2,3,3,3-pentafluoropropyl)phosphate, triphenyl phosphite, trimethyl phosphite, triethyl phosphite, tributyl phosphite, dimethyl methylphosphonate, diethyl ethylphosphonate, ethoxy pentafluorocyclotriphosphazene, phenoxy pentafluorocyclotriphosphazene, hexamethoxycyclotriphosphazene and ionic liquid.
[0060] In a second aspect, the present application also provides a cluster electrolyte, comprising: complex molecules generated by complex reaction between cations of an organic electrolyte lithium salt and organic solvent molecules, and anions of the organic electrolyte lithium salt located in the solvation sheath of the cations.
[0061] In some embodiments, the organic electrolyte lithium salt accounts for 45%-95% of the cluster electrolyte.
[0062] In some embodiments, the organic electrolyte lithium salt includes at least one of lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium di(polyfluoroalkylsulfonyl)imide, lithium di(polyfluoroalkoxysulfonyl)imide, tri(trifluoromethylsulfonyl)methyl lithium, lithium bisoxalatoborate, and lithium difluorooxalatoborate.
[0063] In some embodiments, the organic solvent includes at least one of a carbonate solvent, a fluorocarbon solvent, an ether solvent, a fluoroether solvent, a carboxylate solvent, a sulfite solvent, a phosphate solvent, and a sulfone solvent.
[0064] In some embodiments, the carbonate solvent includes at least one of ethylene carbonate, 1,2-dimethylethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dibutyl carbonate and derivatives thereof.
[0065] In some embodiments, the fluorocarbonate solvent includes at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoromethylethylene carbonate, methyl trifluoroethyl carbonate, fluorodimethyl carbonate and derivatives thereof.
[0066] In some embodiments, the ether solvent includes at least one of tetrahydrofuran, dioxolane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether and derivatives thereof.
[0067] In some embodiments, the fluoroether solvent is a linear fluoroether with the structural formula: R 1 -OR 2 , where R 1 and R 2 It may be methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, isobutyl, tert-butyl, pentyl, isopentyl, etc., or a group in which some or all of the hydrogen atoms are substituted with fluorine.
[0068] In some embodiments, the fluoroether solvent includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, 1,1,1,3,3,3-hexafluoropropyl-methyl ether, 1,1,1,2,3,3-hexafluoropropyl-2,2,3,3-tetrafluoropropyl ether and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether.
[0069] In some embodiments, the carboxylate solvent includes at least one of methyl formate, methyl acetate, ethyl acetate and derivatives thereof.
[0070] In some embodiments, the sulfite solvent includes at least one of dimethyl sulfite, diethyl sulfite and derivatives thereof.
[0071] In some embodiments, the phosphate ester solvent includes at least one of trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, ethylene ethyl phosphate, and tris(2,2,2-trifluoroethyl) phosphate.
[0072] In some embodiments, the sulfone solvent includes at least one of dimethyl sulfoxide and sulfolane.
[0073] Thirdly, reference Figure 2 The present application also provides a method for preparing a composite electrode, comprising: uniformly dry-mixing the cluster electrolyte described in the second aspect of the present application or the cluster electrolyte prepared by the preparation method described in the first aspect of the present application with an electrode active material and a conductive agent to obtain a first mixture; adding a binder to the first mixture and applying high shear force to mix, fiberizing the binder to obtain a second mixture; rolling or extruding the second mixture to obtain a self-supporting electrode film; hot-pressing the self-supporting electrode film and a current collector to obtain a composite electrode; and die-cutting the composite electrode to obtain the composite electrode.
[0074] In some embodiments, the mass ratio of the cluster electrolyte, the electrode active material, the binder and the conductive agent is (5-30):(60-85):(3-10):(1-10).
[0075] In some embodiments, the electrode active material is a positive electrode active material or a negative electrode active material; the positive electrode active material includes at least one of lithium cobalt oxide, high-pressure lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, nickel cobalt manganese ternary material, nickel cobalt aluminum ternary material, lithium-rich manganese-based material and lithium manganese oxide, and the negative electrode active material includes at least one of carbon-based material, silicon-based material, silicon-carbon composite material, lithium titanate, tin-based material, germanium-based material and black phosphorus-based material.
[0076] In some embodiments, the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads and hard carbon; the silicon-based material includes at least one of elemental silicon and silicon monoxide; the silicon-carbon composite material includes a complex of elemental silicon and at least one of artificial graphite and natural graphite or a complex of silicon monoxide and at least one of artificial graphite and natural graphite; the tin-based material includes at least one of elemental tin or tin oxide; the germanium-based material includes at least one of elemental germanium or germanium oxide; and / or the black phosphorus-based material includes black phosphorus and antimony-doped black phosphorus.
[0077] In some embodiments, the conductive agent includes at least one of electric carbon black, carbon nanotubes, nanocarbon fibers, and graphene.
[0078] In some embodiments, the binder includes polytetrafluoroethylene.
[0079] In some embodiments, the current collector is copper foil, aluminum foil, nickel foil, stainless steel foil or a conductive plastic film.
[0080] In a fourth aspect, the present application provides a composite pole piece prepared by the preparation method described in the third aspect of the present application.
[0081] In a fifth aspect, the present application also provides a lithium battery, which includes: at least two composite pole pieces provided in the present application, serving as the positive pole piece and the negative pole piece of the lithium battery respectively; and a diaphragm arranged between the composite electrodes, wherein the diaphragm is a solid electrolyte diaphragm or a quasi-solid electrolyte diaphragm.
[0082] Since the composite electrode sheet contains a cluster electrolyte, it can have ion conductivity without being soaked in an electrolyte. In the preparation process of the battery, no electrolyte needs to be added, thereby reducing the process steps.
[0083] In some embodiments, the solid electrolyte membrane includes one or more of a polymer solid electrolyte membrane, an oxide solid electrolyte membrane, a sulfide solid electrolyte membrane, a halide solid electrolyte membrane, and an organic / inorganic composite solid electrolyte membrane. In some embodiments, the polymer electrolyte membrane includes one or more of a polyethylene oxide (PEO)-based solid electrolyte membrane and a polyvinylidene fluoride (PVDF)-based solid electrolyte membrane.
[0084] In some embodiments, the quasi-solid electrolyte membrane includes one or more of a polymer quasi-solid electrolyte membrane, an oxide quasi-solid electrolyte membrane, a sulfide quasi-solid electrolyte membrane, a halide quasi-solid electrolyte membrane, and an organic / inorganic composite quasi-solid electrolyte membrane. In some embodiments, the polymer quasi-solid electrolyte includes one or more of a polyoxyethylene quasi-solid electrolyte membrane, a polyvinylidene fluoride quasi-solid electrolyte membrane, and a polyolefin reference solid electrolyte membrane.
[0085] The specific implementation methods of the present application are further described below in combination with examples and comparative examples, but the present application is not limited to the following examples. The following examples are all conventional experimental methods unless otherwise specified; the reagents and materials used can be obtained from commercial channels unless otherwise specified.
[0086] Preparation of cluster electrolytes
[0087] Example 1
[0088] 6.2g of lithium trifluoromethanesulfonate was added to a mixed organic solvent of 14.5g of ethylene carbonate and 21.3g of ethyl methyl carbonate, and the mixture was stirred thoroughly to completely dissolve the lithium trifluoromethanesulfonate. The mixture was stirred for 2h to form a cluster electrolyte precursor. The precursor was then heated at 100°C at normal pressure for 4h to obtain a cluster electrolyte.
[0089] Example 2
[0090] Take 5.7g of lithium bis(trifluoromethylsulfonyl)imide and add it to a mixed solvent consisting of 8.4g of propylene carbonate, 15.0g of dimethyl carbonate and 1.5g of fluoroethylene carbonate, stir it thoroughly to completely dissolve the lithium bis(trifluoromethylsulfonyl)imide, and continue stirring for 2h to form a cluster electrolyte precursor. Then heat the precursor at 120°C at normal pressure for 2h to obtain a cluster electrolyte.
[0091] Example 3
[0092] Take 1.5g of lithium bis(fluorosulfonyl)imide and 2.3g of lithium bis(trifluoromethyl)sulfonyl)imide and add them to a mixed solvent consisting of 4.5g of dimethyl carbonate, 5.6g of ethyl methyl carbonate and 0.4g of vinylene carbonate, stir them thoroughly to completely dissolve the lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethyl)sulfonyl)imide, and continue stirring for 2h to form a cluster electrolyte precursor. Then, heat the precursor at 100°C in vacuum for 2h to obtain a cluster electrolyte.
[0093] Example 4
[0094] Take 3.2g of tris(trifluoromethylsulfonyl)methyl lithium and add it to a mixed solvent consisting of 6.5g of ethylene carbonate, 3.2g of dimethyl carbonate, 2.1g of ethylene glycol dimethyl ether and 0.4g of ethoxypentafluorocyclotriphosphazene, stir it thoroughly to completely dissolve the tris(trifluoromethylsulfonyl)methyl lithium, continue stirring for 2h to form a cluster electrolyte precursor. Then heat the precursor at 80°C in vacuum for 6h to obtain a cluster electrolyte.
[0095] Testing of cluster electrolytes
[0096] Ionic conductivity test
[0097] A symmetrical cell of blocking electrode / cluster electrolyte / blocking electrode was prepared using a polished stainless steel sheet as a blocking electrode, and the impedance of the cluster electrolyte prepared in Example 1, Example 2, Example 3 and Example 4 was tested by electrochemical impedance spectroscopy (EIS) at room temperature. The room temperature ionic conductivity of the cluster electrolyte was calculated according to the formula: σ = d / (R*S), where σ is the ionic conductivity, d is the thickness of the cluster electrolyte, R is the impedance of the cluster electrolyte, and S is the effective contact area between the blocking electrode and the cluster electrolyte.
[0098] Electrochemical Window Test
[0099] A plugging electrode / cluster electrolyte / metallic lithium test cell was prepared using a polished stainless steel sheet as a plugging electrode and metallic lithium as a counter electrode. The electrochemical window of the cluster electrolytes prepared in Example 1, Example 2, Example 3 and Example 4 was tested by linear sweep voltammetry (LSV) at room temperature. The test voltage range was 2.0 to 6.0 V, and the scan rate was 5 mV / s.
[0100] The test results are shown in Table 1:
[0101] Table 1 Room temperature ionic conductivity and electrochemical window of cluster electrolytes
[0102]
[0103] It can be seen from Table 1 that the cluster electrolytes prepared by Examples 1 to 4 of the present application have good room temperature ionic conductivity and a wider electrochemical window (the electrochemical window of liquid and gel electrolytes is usually 1.0V to 4.5V, while the electrochemical window of the cluster electrolyte provided in the present application is 1.0V to 5.2V). Therefore, the cluster electrolyte can be applied to battery systems with high-voltage positive electrode materials, which can enable lithium batteries to have higher energy density, cycle life and safety.
[0104] Preparation of composite pole piece
[0105] Example 5 Preparation of positive electrode sheet
[0106] Take 29.9g of high-voltage lithium cobalt oxide, 1.3g of conductive carbon black and 3.8g of the cluster electrolyte prepared in Example 2, and mix them with a stirrer to mix the three evenly to obtain a first mixture. Add 2.0g of polytetrafluoroethylene dry powder, use a jet mill to act on the mixture, make the polytetrafluoroethylene fully fiberized and mixed evenly, and obtain a second mixture. Then the second mixture is repeatedly rolled to form a self-supporting electrode film, and the prepared self-supporting electrode film is hot-pressed with carbon-coated aluminum foil to obtain a composite electrode, and the composite electrode is cut with a punching slicer to obtain a composite positive electrode sheet with a diameter of 16mm.
[0107] Example 6 Preparation of positive electrode sheet
[0108] Take 27.6g of ternary material NCM811, 1.0g of conductive carbon black and 3.5g of cluster electrolyte prepared in Example 3, and mix them with a stirrer to mix them evenly to obtain a first mixture. Add 1.6g of polytetrafluoroethylene dry powder, use a jet mill to act on the mixture, make the polytetrafluoroethylene fully fiberized and mixed evenly, and obtain a second mixture. Then the second mixture is repeatedly rolled to form a self-supporting electrode film, and the prepared self-supporting electrode film is hot-pressed with carbon-coated aluminum foil to obtain a composite electrode, and the composite electrode is cut with a punching slicer to obtain a composite positive electrode sheet with a diameter of 16mm.
[0109] Example 7 Preparation of positive electrode sheet
[0110] Take 28.7g of ternary material NCM523, 1.2g of conductive carbon black and 4.8g of cluster electrolyte prepared in Example 1, mix them, use a stirrer to fully stir the three to mix them evenly, and obtain a first mixture. Add 1.8g of polytetrafluoroethylene dry powder, use a jet mill to act on the mixture, make the polytetrafluoroethylene fully fiberized and mixed evenly, and obtain a second mixture. Then the second mixture is repeatedly rolled to form a self-supporting electrode film, and the prepared self-supporting electrode film is hot-pressed with carbon-coated aluminum foil to obtain a composite electrode, and the composite electrode is cut with a punching slicer to obtain a composite positive electrode sheet with a diameter of 16mm.
[0111] Example 8 Preparation of negative electrode sheet
[0112] 13.5g of artificial graphite, 0.6g of conductive carbon black and 2.6g of the cluster electrolyte prepared in Example 4 were mixed, and the three were fully stirred by a stirrer to mix them evenly to obtain a first mixture. 1.2g of polytetrafluoroethylene dry powder was added, and a jet mill was used to act on the mixture to fully fiberize the polytetrafluoroethylene and mix it evenly to obtain a second mixture. The second mixture was then repeatedly rolled to form a self-supporting electrode film, and the prepared self-supporting electrode film was hot-pressed with a carbon-coated copper foil to obtain a composite electrode, and the composite electrode was cut with a punching slicer to obtain a composite negative electrode sheet with a diameter of 17mm.
[0113] Preparation of lithium batteries
[0114] Preparation of lithium battery: The composite positive electrode plates obtained in Examples 5 to 7 and the composite negative electrode plates obtained in Example 8 are used as the separator. The diaphragm is a polyvinylidene fluoride-based solid electrolyte diaphragm with good ionic conductivity. The battery assembly process is consistent with the conventional button battery assembly process, except that the injection process is omitted. After the battery is sealed, it is placed in a 40°C temperature box for 1 hour. The battery is taken out and cooled to room temperature for electrical performance testing. The battery performance test results are shown in Table 2, using the example number of the positive electrode plate as the battery number:
[0115] Table 2 Discharge capacity and cycle performance of solid-state batteries at different rates
[0116]
[0117] As can be seen from Table 2, the lithium battery assembled with the composite electrode provided by the patent of the present invention can fully utilize the gram capacity of different positive electrode materials and has good cycle performance. This is because the composite electrode prepared by the technical solution of the present application uniformly contains cluster electrolytes. The composite electrodes prepared in Examples 5 to 8 utilize the characteristics of high room temperature ionic conductivity and wide electrochemical window of cluster electrolytes, which are compatible with different electrode materials, so that the lithium battery can achieve good charge and discharge cycles without an external electrolyte. The composite electrode provided by this application has good electrochemical properties, and the preparation process is simple and reliable, the production cost is low, the feasibility is high, and it has good application prospects, laying a solid foundation for the research and development and industrialization of new high-performance lithium batteries.
[0118] The beneficial effects of the cluster electrolyte, composite electrode and preparation method thereof provided in the present application include but are not limited to the following:
[0119] Compared with liquid electrolytes and gel electrolytes, the cluster electrolyte provided in this application has higher thermal stability and safety, a wider electrochemical window, and is compatible with high-voltage positive electrode materials; compared with solid electrolytes, it has low production costs, a simple and easy-to-control preparation process, and is easy to achieve large-scale production.
[0120] The lithium battery prepared by the composite electrode including the cluster electrolyte provided in the present application has better thermal stability and safety compared with conventional liquid lithium batteries; compared with solid-state batteries, the production cost is low and large-scale production is easy to achieve.
[0121] In addition, the preparation method of lithium batteries using composite pole pieces is simpler than that of conventional liquid lithium batteries, reduces the liquid injection process, and helps to improve production efficiency.
[0122] In summary, after reading the contents of this application, those skilled in the art will appreciate that the aforementioned application contents may be presented only in an exemplary manner and may not be restrictive. Although not explicitly stated herein, those skilled in the art will appreciate that this application is intended to encompass various reasonable changes, improvements and modifications to the embodiments. These changes, improvements and modifications are within the spirit and scope of the exemplary embodiments of this application.
[0123] It should be understood that the term “and / or” used in this embodiment includes any or all combinations of one or more of the associated listed items.
[0124] Similarly, it should be understood that the terms "comprise", "comprising", "including" or "comprising", when used in this application document, indicate the presence of the recorded features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or groups thereof.
[0125] It should also be understood that although the terms first, second, third, etc. can be used to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish an element from another element. Therefore, without departing from the teaching of the application, the first element in some embodiments can be called the second element in other embodiments.
Claims
1. A cluster electrolyte, characterized in that: include: The complex molecule is generated by the complex reaction between the cation of the organic electrolyte lithium salt and the organic solvent molecule, and the anion of the organic electrolyte lithium salt is located in the solvation sheath of the cation.
2. The cluster electrolyte according to claim 1, characterized in that: The organic electrolyte lithium salt includes at least one of lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium bis(polyfluoroalkylsulfonyl)imide, lithium bis(polyfluoroalkoxysulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium, lithium bisoxalatoborate and lithium difluorooxalatoborate.
3. The cluster electrolyte according to claim 1, characterized in that: The organic solvent includes at least one of a carbonate solvent, a fluorocarbon solvent, an ether solvent, a fluoroether solvent, a carboxylate solvent, a sulfite solvent, a phosphate solvent and a sulfone solvent.
4. A method for preparing a cluster electrolyte, characterized in that: include: dissolving an organic electrolyte lithium salt in an organic solvent to obtain a precursor; as well as The precursor is heated and / or negative pressure is applied, so that the organic solvent molecules in the precursor are combined with the electrolyte lithium salt to form a cluster electrolyte, and the organic solvent that has not formed the cluster electrolyte is completely volatilized, wherein the cluster electrolyte includes: complex molecules generated by complex reaction between cations of the organic electrolyte lithium salt and organic solvent molecules, and anions of the organic electrolyte lithium salt located in the solvation sheath of the cations.
5. The preparation method according to claim 4, characterized in that: The organic electrolyte lithium salt includes at least one of lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium bis(polyfluoroalkylsulfonyl)imide, lithium bis(polyfluoroalkoxysulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium, lithium bisoxalatoborate and lithium difluorooxalatoborate.
6. The preparation method according to claim 4, characterized in that: The organic solvent includes at least one of a carbonate solvent, a fluorocarbon solvent, an ether solvent, a fluoroether solvent, a carboxylate solvent, a sulfite solvent, a phosphate solvent and a sulfone solvent.
7. The preparation method according to claim 4, characterized in that: In the step of dissolving the organic electrolyte lithium salt in an organic solvent to obtain a precursor, an additive is added to the organic solvent, wherein the additive includes at least one of a performance optimizer and a flame retardant.
8. The preparation method according to claim 7, characterized in that: The performance optimizer includes at least one of vinylene carbonate, vinylethylene carbonate, ethylene sulfate, ethylene sulfite, propylene sulfate, propylene sulfite, 4-methylethylene sulfate, 4-methylethylene sulfite, 1,4-butane sultone, 1,3-propane sultone, cyclohexylbenzene, tris(trimethylsilane)phosphate, tris(trimethylsilane)phosphite, tris(trimethylsilane)borate, succinonitrile, adiponitrile, pentafluoropropionic anhydride, fluoroethylene carbonate, lithium difluorooxalatoborate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorophosphate and lithium nitrate; and / or The flame retardant includes at least one of tris(2,2,2-trifluoroethyl)phosphite, tris(4-fluorophenyl)phosphine, tris(2,2,3,3,3-pentafluoropropyl)phosphate, triphenyl phosphite, trimethyl phosphite, triethyl phosphite, tributyl phosphite, dimethyl methylphosphonate, diethyl ethylphosphonate, ethoxy pentafluorocyclotriphosphazene, phenoxy pentafluorocyclotriphosphazene, hexamethoxycyclotriphosphazene and ionic liquid.
9. A method for preparing a composite pole piece, characterized in that: include: Uniformly dry-mixing the cluster electrolyte according to any one of claims 1 to 3 or the cluster electrolyte prepared by the preparation method according to any one of claims 4 to 8 with an electrode active material and a conductive agent to obtain a first mixture; Adding a binder to the first mixture and applying high shear force to mix the mixture to fiberize the binder to obtain a second mixture; Rolling or extruding the second mixture to obtain a self-supporting electrode film; Hot pressing the self-supporting electrode film and the current collector to obtain a composite electrode; as well as The composite electrode is die-cut to obtain the composite electrode piece.
10. The preparation method according to claim 9, characterized in that: The electrode active material is a positive electrode active material or a negative electrode active material; the positive electrode active material includes at least one of lithium cobalt oxide, high-pressure lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium-rich manganese-based material and lithium manganese oxide, and the negative electrode active material includes at least one of carbon-based material, silicon-based material, silicon-carbon composite material, lithium titanate, tin-based material, germanium-based material and black phosphorus-based material; and / or The conductive agent comprises at least one of electric carbon black, carbon nanotubes, carbon nanofibers and graphene; and / or The binder comprises polytetrafluoroethylene; and / or The current collector is copper foil, aluminum foil, nickel foil, stainless steel foil or conductive plastic film.
11. A composite pole piece, characterized in that: The method is prepared by any one of claims 9 to 10.
12. A lithium battery, characterized in that: include: At least two composite pole pieces as claimed in claim 11; as well as The separator is arranged between the composite electrodes, and the separator is a solid electrolyte separator or a quasi-solid electrolyte separator.
Citation Information
Cited By
Complex hydride based-electrolyte and Li-S battery using the same
KR102983537B1
